A physics-based TCAD framework for NBTI. (April 2023) - Tiwari, Ravi; Duan, Meng; Bajaj, Mohit; Dolgos, Denis; Smith, Lee; Wong, Hiu Yung; Mahapatra, Souvik
Highlights: A fully physical TCAD framework to model the NBTI is validated with differently processes MOSFET measured data. RD model with ABDWT model for interface trap generation, RDD model for bulk trap generation, ABDWT model for hole trapping is used. Framework Validation in TCAD in 3D FinFETs and GAA-FETs is in progress. Abstract: A physics-based framework is incorporated in TCAD to model the primary mechanisms responsible for Negative Bias Temperature Instability (NBTI) in P channel High-K Metal Gate (HKMG) MOSFETs. Three underlying mechanisms are treated including interface trap generation-passivation via a Reaction-Diffusion (RD) model and its charge occupancy via an Activated Barrier Double Well Thermionic (ABDWT) model, hole trapping and de-trapping in pre-existing defects in the gate stack are modeled via an ABDWT model, and bulk trap generation-passivation is modeled via a Reaction-Diffusion-Drift (RDD) model. The framework is used to model measured NBTI time-kinetics for DC stress-recovery and various mixed DC-AC gate pulse segments for planar devices. Furthermore, the same framework is also used to test NBTI behavior in 3D FinFETs.